ChemInform Abstract: Diffusion‐Assisted Synthesis of Co2FeSn Heusler Nanoparticles and Their Magnetic Properties. Issue 17 (April 2016) - Li, Pengpeng; Kou, Xinli
Abstract: Co2 FeSn Heusler nanoparticles (5—12 nm particle size) are prepared by boiling Co2 Fe and Sn nanoparticles in tetraethylene glycol (stirring, 230 °C, 24 h) which results in diffusion of molten Sn into Co2 Fe nanoparticles.